Synthesis of Biodiesel by Pyrolysis of Castor Oil - Datta, Sudipta; Chavan, Prakash; Saha, Sujan; Sahu, Gajanan; Mall, B.K. (Asian Journal of Chemistry, 2011)
In this study, pyrolysis route was selected to produce the biodiesel from commercial grade castor oil. Three temperatures, 250, 300 and 350 ºC were chosen with variable residence time from 10-30 min. All the reactions were carried out in the presence of hydrogen gas varying the initial pressure from 5-20 kg/cm2. The fuel properties of the biodiesel like calorific value, cetane index, viscosity, cloud point, pour point etc., were determined and it was found that the properties are very much closed to petroleum diesel. The maximum yield of 76 % was obtained in the present study. However, considering the fuel properties it has been observed that 350 ºC reaction temperature, 20 min residence time and 15-20 kg/cm2 initial hydrogen pressure can be the most suitable condition for the production of biodiesel from the castor oil.